Decay control and quality of individually film-wrapped lemons treated with sodium carbonate. (February 2020) - D'Aquino, Salvatore; Continella, Alberto; Gentile, Alessandra; Dai, Suming; Deng, Ziniu; Palma, Amedeo
Abstract: The efficacy of 3-min-dip treatments with 3% sodium carbonate solutions at 20 or 50 °C was tested on lemons individually, not hermetically, sealed within low density polyethylene (LDPE) bags. Before sealing, treated lemons were rinsed (SCR) or not rinsed (SC) with fresh water. SC treatment almost completely inhibited green mold ( Penicillium digitatum ) development in wound-artificially inoculated lemons both wrapped and not wrapped after 15 d at 5 °C followed by 7 d at 20 °C or in those stored for 10 d at 20 °C. In SCR lemons, decay control was inferior, especially in wrapped lemons treated at 20 °C. Similar results were achieved with sound fruit inoculated 24 h before the treatments and stored for 30 d at 20 °C. SC and, at a less extent, SCR treatments increased dramatically mass loss of un-wrapped fruit compared to control fruit, whereas in wrapped fruit overall mass loss was almost completely inhibited. Wrapping the fruit in LDPE bags allowed to maintained fruit freshness and firmness and chemical quality along the whole storage time, regardless the treatments. Highlights: Sodium carbonate effectively controlled decay in fruit not rinsed after treatment. Decay control of sodium carbonate treated and rinsed fruit was modest. Sodium carbonate increased water loss and hastened ageing of treated fruit. Individual film wrapping inhibited water loss and ageing but promoted decay. Film wrapping sodium carbonate treated fruit preserved freshness and controlled decay.